2015
DOI: 10.1371/journal.pone.0120425
|View full text |Cite
|
Sign up to set email alerts
|

Blood-Based Protein Biomarker Panel for the Detection of Colorectal Cancer

Abstract: BackgroundThe majority of colorectal cancer (CRC) cases are preventable by early detection and removal of precancerous polyps. Even though CRC is the second most common internal cancer in Australia, only 30 per cent of the population considered to have risk factors participate in stool-based test screening programs. Evidence indicates a robust, blood-based, diagnostic assay would increase screening compliance. A number of potential diagnostic blood-based protein biomarkers for CRC have been reported, but all l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
48
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(51 citation statements)
references
References 48 publications
(43 reference statements)
3
48
0
Order By: Relevance
“…The study showed a sensitivity of 73% and specificity of 95% in detecting CRC [23]. The sensitivity of detecting early stage cancer was moderate with 59% in stage I and 84% in stage II.…”
Section: Resultsmentioning
confidence: 99%
“…The study showed a sensitivity of 73% and specificity of 95% in detecting CRC [23]. The sensitivity of detecting early stage cancer was moderate with 59% in stage I and 84% in stage II.…”
Section: Resultsmentioning
confidence: 99%
“…Multi-omics sequencing technologies have increased the number of genetic biomarkers 2 . Single or combination biomarkers are increasingly being analyzed and tested in the context of genes, RNA, or proteins [3][4][5][6] . Many strategies for uncovering biomarkers exist, such as mass-spectrometry-based, protein arrays and gene-expression profiling.…”
Section: Introductionmentioning
confidence: 99%
“…However, inclusion of a specific set of biomarkers in the panel will be crucial. 12,13 For example, Levels of PSA in normal subjects range between 0.5 – 2 ng/mL and 4 – 10 ng/mL for cancer patients while for IL-6 normal levels are <7 pg/mL and for cancer patients up to 5 ng/mL, respectively. Given this situation, we need to develop approaches such that these biomarkers can be placed together on a single detection assay.…”
Section: Introductionmentioning
confidence: 99%